Best bilinear approximations of the classes $S^{Ω}_{p, θ}B$ of periodic functions of many variables - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
We obtain exact-order estimates of the best bilinear approximations of classes $S^{Ω}_{p, θ}B$ of periodic functions of many variables in the space $L_q$ for some relations between parameters $p, q, θ$.